(untitled) (GnosisWisdom, 2025)
The guinea pig (Cavia porcellus) is a species of economic, nutritional and cultural importance in several regions of the Andes, especially in Peru. However, its production is frequently threatened by multiple parasitic diseases that affect its health, welfare and zootechnical performance. This scientific review compiles, analyzes and synthesizes updated information on the main parasites affecting guinea pigs, both endoparasites and ectoparasites, detailing their clinical, productive and economic impact. Scientific articles published in the last five years in databases such as Scopus, PubMed and SciELO were reviewed. The results indicate that protozoa such as Eimeria spp, gastrointestinal nematodes such as Trichostrongylus spp, and ectoparasites such as Gyropus ovalis represent the most prevalent and detrimental agents in guinea pig breeding. Antiparasitic resistance, diagnostic challenges and integrated control strategies are also discussed. This review provides a useful overview for researchers, producers and veterinary professionals interested in improving the health and productivity of this key species.